Long-term prognostic value of elevated pentraxin 3 in patients undergoing primary angioplasty for ST-elevation myocardial infarction. Issue 7 (November 2015) - Akgul, Ozgur; Baycan, Omer Faruk; Bulut, Umit; Somuncu, Mustafa Umut; Pusuroglu, Hamdi; Ozyilmaz, Sinem; Gul, Mehmet; Demir, Ali Riza; Yilmaz, Emre; Yazan, Serkan; Kokturk, Uğur; Cetin, Ilyas; et al.
<x xml:space="preserve">Abstract</x> Objectives The prognostic value of pentraxin 3 (PTX3) has been documented in patients with acute coronary syndrome. However, its long-term prognostic value in acute ST-segment elevation myocardial infarction (STEMI) remains unclear. The aim of this study was to evaluate the prognostic value of PTX3 in patients with STEMI undergoing a primary percutaneous coronary intervention (PCI). Methods We prospectively enrolled 499 consecutive STEMI patients undergoing primary PCI. The high-PTX3 group (n=141) was defined as having values in the third tertile (≥3.2 ng/ml) and the low-PTX3 group (n=358) included patients with values in the lower two tertiles (<3.2 ng/ml). Results The patients in the high-PTX3 group were older (mean age 54.3±11.8 vs. 58.5±13.1 years, P=0.002). Higher in-hospital cardiovascular mortality and 2-year all-cause mortality rates were observed in the high-PTX3 group (9.9 vs. 2.8%, respectively, P<0.001; 21 vs. 6.2%, respectively, P<0.001). In a Cox multivariate analysis, a high admission PTX3 value (>3.2 ng/ml) was found to be an independent predictor of 2-year all-cause mortality (odds ratio: 2.3, 95% confidence interval: 1.20–4.90, P=0.025). Conclusion These results suggest that a high admission PTX3 level was associated with increased in-hospital cardiovascular mortality and 2-year all-cause mortality in patients with STEMI undergoing primary PCI.